Pengaruh Model CIRC terhadap Kemampuan Menulis Karangan Narasi Kelas IV SD - Dian Kirana Dewi; Haryadi Haryadi (Journal of Elementary School (JOES), 2022)
This study aims to find out whether there is an influence on the use of the Cooperative Integrated Reading and Composition (CIRC) learning model on the ability to read students' narrative essays. This research uses a descriptive type of research, where the source of the data obtained is from discussion activities during the learning of grade IV students of SD Berangah. The instrument used in this study was to use an observation sheet. The analysis technique used to determine the reading comprehension of students' narrative essays is the technique of skin data analysis techniques. The results showed that there was an influence of the Cooperative Integrated Reading and Composition (CIRC) type cooperative learning model on the ability to read narrative essays of grade IV students of SD Berangah. This can be seen from the ability to read narrative essays of grade IV students both after being implemented by the CIRC learning model. Keywords: CIRC Model, Writing Ability, Essay, Narrative.